PENGARUH PERKEMBANGAN IPTEK TERHADAP PERMASALAHAN HAKI - Munsharif Abdul Chalim (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Intellectual Property Rights’ issues are growing problems in accordance with the development of science and technology. As examples of developments in biotechnology with the technology of genetic engineering led to the birth of the need to protect the results of biotechnology engineering. In developed countries Intellectual Property Rights has become part of everyday society, so that science and technology development in the country are always oriented to the protection of Intellectual Property Rights. Excellence in aspects of trade can be owned by developed countries because one of them is determined by the comparative advantage of the ability of science and technology that is related to the field of intellectual property rights. Keywords: IPRs, law protection, economic benefit